New Genera, Species, and observations on the biology of Antarctic Valvatida (Asteroidea) - Mah, Christopher L. (Zootaxa, 2023)
Assessment of Antarctic taxonomic diversity for asteroids and other taxa for poorly studied or unknown regions, such as the deep-sea, will be important for our understanding of these understudied habitats. Eleven new species and a new genus are described from three families (Asterinidae, Goniasteridae, Solasteridae) within the Valvatida, nearly all of which were collected from deep-sea settings below 1000 m by the US Antarctic Research Program in the 1960s. A new subfamily, the Kampylasterinae subfam. nov. is designated for Kampylaster and Astrotholus nov. gen. which were supported as sister taxa on a monophyletic clade within the Asterinidae. Astrotholus nov. gen. is described to accommodate “Anseropoda” antarctica and four new bathyal and abyssal species, which are a significant morphological divergence from the typological definition of Anseropoda. New species of the goniasterid Notioceramus and the solasterid Paralophaster are also described from bathyal depths (2000–3000 m). Paralophaster ferax n. sp. is among the deepest asteroids known to brood, is the first brooding species within Paralophaster and the second species in the Solasteridae known to brood. Following examination of the type and molecular data, Lophaster densus is found to be included within Paralophaster. A review of Antarctic Lophaster species shows additional specimens of Lophaster abbreviatus which support it as a distinct species from Lophaster stellans. New occurrence data for bathyal Antarctic Asteroidea as well as unusual-gut content observations of shallower-water species are also included.